The games bible over 300 games--the rules, the gear, the strategies - Anderson, Leigh (New York Workman Publishing, 2010)
A comprehensive compendium celebrating the old-fashioned pleasure of pure play.
Putting the fun back into parties -- Icebreakers -- Guessing games -- Indoor frolics -- Conversation games -- Literary & word games -- Right-brain games -- Games of general cleverness -- Victorian parlor games -- Holiday games -- Games for gamblers & bluffers -- Trivia games -- A card-game refresher -- Brainy games for two -- Games for a weekend away -- Impromptu games -- Outdoor games -- Lawn games.
Includes index.
Keywords: Adult party games; Amusements